Hành vi tiêu dùng bền vững: Sự khác biệt giữa các nhóm người tiêu dùng Việt Nam theo lý thuyết lưỡng nan xã hội - Ho Huy , Tuu (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This study defines and measures sustainable consumption behaviors in terms of a multidimensional construct consisting of three components: Economical consumption, consumption behaviors for good health, and compliance with environmental regulations. A segmentation approach based on social dilemmas (self-transcendence ​​vs. self-enhancement and consideration of future consequences (CFC)-immediate vs. CFC-future) using K-cluster analysis, grouping, and ANOVA. A quota sample of 700 consumers in 05 cities (Ha Noi, Tuy Hoa, Nha Trang, HCMC, and Can Tho) is used. The results show the differences in sustainable consumption behaviors between 04 consumer segmentation with increasing levels: Immediate – Individual, Immediate – Social, Future – Individual, and Future – Social. Based on these findings, practical implications about the values and time perspectives are suggested to promote Vietnamese consumers’ sustainable consumption behaviors.
Keywords: Sustainable consumption behaviors; Social dilemmas; Segmentation